(NsONETY(B. (NsON W LETN@@ NO^X (B/s - (N{EKSPIR(B, (NwILXQM(B,s; (NfILIPOW(B, (Na(B. (Nn(B.,s; (NaWERKIEWA(B, (Nd(B.,s ((NmOSKWA (B:s (NrIPOL KLASSIK(B,s, 2010)
(NkNIGA M)QÆSTITX SONETI TA KOMEDÆ@ (B" (NsON W LETN@@ NO^X(B" (NwÆLXQMA {EKSPÆRAs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NaNGL)QÆJSXKA LÆTERATURAs)E -- (NsONETIs; (N{EKSP)QÆRs)E; (NSONETIs; (NsON L)QÆTNXOÇ NO^Æs)E; (NtEZEJ(B, (N|GEJs; (NiPPOLITAs; (NgERMIQs; (NeLENAs; (NdEMETRIJs; (NlIZANDERs